2015
DOI: 10.18860/neu.v0i0.3013
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Fisis Membran Biofilter Rokok Dengan Variasi Daun, Biji Dan Kulit Delima

Abstract: Analisis fisis membrane biofilter rokok telah dilakukan untuk mengetahui kerapatan dan porositas. Membrane biofilter terbuat dari variasi daun delima, biji delima dan kulit delima. Variasi massa yang digunakan pada masing-masing bahan delima adalah 0.7 gram, 0.8 gram, 0.9 gram dan 1 gram. Matriks yang digunakan pada pembuatan biofilter berbahan delima adalah polyethilene glikol (PEG). Data pengujian kerapatan membran pada biofilter berbahan daun delima terbesar adalah 1.532 g/cm<sup>3</sup> dengan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The greater the porosity of the CMCC, the smaller the density of the CMCC. The smaller the density indicates the greater the number of pores and the wide pore size [20]. If the porosity of the CMCC is too large, the remazol red dye molecules and other organic compounds in the batik liquid waste can pass through the CMCC.…”
Section: Application Of Cmcc On Batik Liquid Wastementioning
confidence: 99%
“…The greater the porosity of the CMCC, the smaller the density of the CMCC. The smaller the density indicates the greater the number of pores and the wide pore size [20]. If the porosity of the CMCC is too large, the remazol red dye molecules and other organic compounds in the batik liquid waste can pass through the CMCC.…”
Section: Application Of Cmcc On Batik Liquid Wastementioning
confidence: 99%
“…There are seven types of free radicals in cigarettes without a biofilter that can be detected by LeyboldHeracus Electron Spin Resonance (ESR), namely Hydroperoxides, CO 2 -, C, Peroxy, O 2 -, CuOx, CuGeO 3 . On the other hand, Biofilter consists of natural ingredients that contain antioxidants as free radical scavengers [7]. Many studies on special filters made from natural ingredients have been shown to capture free radicals in cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%